Challenging dynamics of high-speed train : magnetic levitation superconductivity aerodynamics - Rangwala, Abdulla S., 1943- (New Academic Science, 2021)
Magnetically levitated bullet trains are the most interesting development of the new millennium, recording travel at unheard of speed levels. The train levitates above the tracks using electromagnets to create a nearly frictionless ride, without making contact with the ground. Moving more smoothly and quietly than wheeled mass transit systems, the power needed for levitation is mostly to overcome aerodynamic drag. A confluence of superconductivity and magnetic technologies has produced this spectacular event. Superconducting magnets do not dissipate energy to maintain the magnetic field. A superconductor levitated above a permanent magnet remains in stable equilibrium. Resistance to flow of electric current in the conductor vanishes, so the magnetically levitated coaches operate without external energy. At the same time, however, initial cost of development and installation is prohibitive. This book provides tools for design and operation of a massive locomotive pulling a heavily loaded train through mountainous regions.